2010
DOI: 10.1074/jbc.m109.013011
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Polyphosphate and Energy Metabolism in Mammalian Cells

Abstract: Inorganic polyphosphate (poly P) is a polymer made from as few as 10 to several hundred phosphate molecules linked by phosphoanhydride bonds similar to ATP. Poly P is ubiquitous in all mammalian organisms, where it plays multiple physiological roles. The metabolism of poly P in mammalian organisms is not well understood. We have examined the mechanism of poly P production and the role of this polymer in cell energy metabolism. Poly P levels in mitochondria and intact cells were estimated using a fluorescent mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
178
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(190 citation statements)
references
References 28 publications
11
178
1
Order By: Relevance
“…Simultaneous measurement of mitochondrial (TMRM) and polyP (JC‐D8) signals showed that ∼40% of cellular polyP resides in mitochondria (here and below coefficient of colocalization is a Mander's X; 0.39 ± 0.08, n  = 204 cells; Figure 1a,d). As we reported previously, the level of polyP in mitochondria is dependent on the energy state of mitochondria and can be modified within seconds (Pavlov et al, 2010). …”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Simultaneous measurement of mitochondrial (TMRM) and polyP (JC‐D8) signals showed that ∼40% of cellular polyP resides in mitochondria (here and below coefficient of colocalization is a Mander's X; 0.39 ± 0.08, n  = 204 cells; Figure 1a,d). As we reported previously, the level of polyP in mitochondria is dependent on the energy state of mitochondria and can be modified within seconds (Pavlov et al, 2010). …”
Section: Resultssupporting
confidence: 64%
“…Accumulation of polyP in cellular organelles and vesicles can indicate a specific signaling function. In this study, we found that ∼39% of the total pool of intracellular polyP in astrocytes is located in mitochondria (Figure 1) where it plays a role in bioenergetics (Angelova, Baev, et al, 2016; Pavlov et al, 2010) and calcium handling (Abramov et al, 2007; Baev et al, 2017; Elustondo et al, 2016). The level of polyP in mitochondria has been previously shown to be dependent on the metabolic state and the age of the cells (Pavlov et al, 2010).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In yeast, a genome-wide screen revealed the interdependence of polyP with primary metabolism (29). In mammalian cells, alteration of mitochondrial metabolism affects polyP production (36). It has also been suggested that polyP is an activator or even a constituent of the mitochondrial permeability transition pore (37).…”
Section: Discussionmentioning
confidence: 99%
“…The method of polyP detection using DAPI was first described in the early 1980s. 21 Since that time, this procedure has been used in several studies (some examples are references: 6,8,13,16,[22][23][24][25] ). Emission fluorescence of DAPI shifts to longer wavelengths in the presence of polyP: this change is specific for polyP and is not produced by PPi, DNA, or other anions.…”
Section: Polyphosphate Is Present In Myeloma Cell Linesmentioning
confidence: 99%